Fracture Toughness of High-Manganese Steels with Twip/Trip Effects - Monsalve-Gonzalez, A; Bordone, M (Elsevier Ltd, 2022)
Three high-manganese steels with different carbon contents were investigated in this work, aiming to explore their elastoplastic fracture toughness, fracture micro-mechanisms and microstructural features. J-R curves were obtained according to ASTM E1820-20 by testing C(T) specimens, applying the unloading compliance method to measure crack extension. The TWIP effect (mechanical twinning + dislocation gliding) developed in Steel A and Steel B with carbon contents of 0.84 wt% and 0.54 wt% respectively. On the other hand, Steel C (carbon content of 0.28 wt%), showed strain-induced γFCC → εHCP transformation associated with the TRIP effect. The three steels presented smooth load (P) vs load-line displacement (v) records; i.e., no instability was observed, which allowed the characterization of fracture toughness by means of J-R curves. Fully dimpled fracture surfaces were observed in Steel A and Steel B, whilst Steel C showed small cleavage facets in some sectors that had not indication in the P vs v records. Best performance in terms of fracture behavior was obtained in Steel B and the poorest in Steel C. In addition to the above, the microstructural analysis of the stable crack growth zones in the fractured specimens allowed the identification of several characteristics. © 2022 Elsevier Ltd